GAMBARAN DERAJAT ANEMIA PADA IBU HAMIL DI BPM NY. YUHERLIS SETYOWATI, Amd. Keb DAN BPM NY. HARINI SUGIARTI, Amd. Keb JATIREJO MOJOKERTO - Basuki, Duwi; Rohmatul, Wenny (JURNAL KEPERAWATAN BINA SEHAT, 2015)
Anemia to the pregnant mother become the main problem of bleeding which is the main factor of dying to the mother in indonesia. According to the report of World Health Organization (WHO) in 2008 pre-valence pregnant mother who got zink deficiensy about 35-75%, it also more increased during the aging of pregnancy. Anemia in pregnancy is the mother’s condition in hemoglobin level under 11g% at trimester 1 and 3 or level 10.5g% below to trimester 2. The research aimed to know The Delineation Degree of Anemia to The Mother In Being Pregnant at BPM Mrs. Yuherlis Setyowati, Amd.Keb And BPM Mrs. Harini Sugiati Amd.Keb Jatirejo Mojokerto. The research design was descriptive research in approaching which had been done by observation. The technique of taking the sample was done by non-probability technique sampling in consecutive sampling type, so it was got 35 respondents sample. Gathering of data used observation sheet. The result of the research was got 17 respondents were not anemia (48.6%). Based on the result of the research is expected to all of mother in being pregnant pay attention of the nutrient quality, consume of fe suplement regulary and find the knowledge about factors which relates to anemia.Key words: Anemia Degree, Mother Pregnant